2023
DOI: 10.1021/acsbiomaterials.3c01097
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding Interactions from Nucleobase-Decorated Supramolecular Polymer: Synthesis, Self-Assembly and Biomedical Applications

Fasih Bintang Ilhami,
Yihenew Simegniew Birhan,
Chih-Chia Cheng

Abstract: The fabrication of supramolecular materials for biomedical applications such as drug delivery, bioimaging, wounddressing, adhesion materials, photodynamic/photothermal therapy, infection control (as antibacterial), etc. has grown tremendously, due to their unique properties, especially the formation of hydrogen bonding. Nevertheless, void space in the integration process, lack of feasibility in the construction of supramolecular materials of natural origin in living biological systems, potential toxicity, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…Supramolecular drug delivery systems (SDDSs) offer an effective method to enhance the effectiveness of medications by facilitating processes such as self-assembled into nanostructures and accurate pH-responsive drug release triggered by the acidic state of the tumor’s immediate environment. Numerous studies reported that SDDSs exhibit rapid responsiveness to diverse stimuli within the TME, thus mitigating harm to normal cells and enhancing the effectiveness of chemotherapy medicines against cancer. , For instance, Luan and co-workers developed a thermal-responsive injectable hydrogel formulated with an l -norvaline-based immunomodulating agent, utilizing a diblock copolymer to encapsulate doxorubicin for suppressing abscopal tumors. , Recent research progress in our laboratory successfully developed and applied multiple hydrogen bond-based supramolecular polymers, particularly with emphasis on fabricating SDDSs containing ureido-cytosine (UrCy) quadruple hydrogen-bonded component . For instance, integrating UrCy moieties into the termini of polyethylene glycol results in the creation of a water-soluble UrCy-functionalized polymer (UrCyPEG).…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular drug delivery systems (SDDSs) offer an effective method to enhance the effectiveness of medications by facilitating processes such as self-assembled into nanostructures and accurate pH-responsive drug release triggered by the acidic state of the tumor’s immediate environment. Numerous studies reported that SDDSs exhibit rapid responsiveness to diverse stimuli within the TME, thus mitigating harm to normal cells and enhancing the effectiveness of chemotherapy medicines against cancer. , For instance, Luan and co-workers developed a thermal-responsive injectable hydrogel formulated with an l -norvaline-based immunomodulating agent, utilizing a diblock copolymer to encapsulate doxorubicin for suppressing abscopal tumors. , Recent research progress in our laboratory successfully developed and applied multiple hydrogen bond-based supramolecular polymers, particularly with emphasis on fabricating SDDSs containing ureido-cytosine (UrCy) quadruple hydrogen-bonded component . For instance, integrating UrCy moieties into the termini of polyethylene glycol results in the creation of a water-soluble UrCy-functionalized polymer (UrCyPEG).…”
Section: Introductionmentioning
confidence: 99%